Karakteristik Sirup Jahe Merah (Zingiber Officinale Roscoe Var.Rubrum) Yang Dihasilkan Dari Tiga Jenis Proses Pengolahan - Rolando Correia Galucho Rosa Dos Santos; Diah Kartikawati (Serat Acitya, 2017)
Red ginger (Zingiber officinale Roscoe var. Rubrum) is a tropical plant that is easy to grow in Indonesia. One of the beneficial properties containing oleoresin is to cure colds and boost immunity. Diversification of processed red ginger syrup product is expected to increase the added value. Red ginger syrup is a refreshing drink that is processed with the addition of sugar into the porridge red ginger. This study aims to determine the characteristic of the red ginger syrup produced from three types of processing to test the properties of the chemical properties, physical properties and determine the level of acceptance A-panelists on red ginger syrup. This research has been carried out in the laboratory of Faculty of Agricultural Technology of 17 Agustus 1945 University Semarang.  The study design used is RAK (Random Group) with 3 treatment   (PA= with three treatments and three replications.          The treatments were performed in this study were treated with extraction (PA = extraction precipitation three times, PB = extraction and precipitation one time PC = extraction without precipitation). The results of the data obtained were analyzed using ANOVA (Analysis of Variance). Treatment precipitation extraction three times (PA), extraction precipitation of one times (PB) and extraction without precipitatin (PC) to produce a total value of pH, total acid titration, total sugar brix, water content and the highest antioxidant activity, respectively amounted to 6,33 %, 1,681 %, 56,67 brix, 40,24 % and 72,02 %. While the value of total dissolved solids and high viscosity that is equal to 44,67 mg/L and 104,78 mPa.s. The results of the sensory test analysis favored red ginger syrup is a favorite flavor = 5,73 (rather preffered), aroma= 5,76 (rather preffered) and color= 5,73 (rather preffered).